A preliminary study on the distribution of fruit tree taxa at Ayer Hitam Forest Reserve, Selangor - Lepun, Philip; Edham, Ibrahim; Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 2001)
An assessment on the fruit trees families Burseraceae, Sapindaceae and Meliaceae showed that 714 trees from 10 genera representing 26 species were identified in the 5-ha plot. Sixteen mother trees were identified and all are Burseraceae explaining the high populations compared to Sapidaceae and Meliaceae. Despite the Ayer Hitam Forest Reserve being not fully recovered from the effects of previous logging activities, the diversity of fruit trees present is commendable in supplying food to different wildlife.